The Political Economy of Makerere Reforms via a Qualitative Approach. An Interview with the Professor Ruth Mukama - (:unkn) unknown (My University, 2014)
The famous and historical Ugandan institution of higher education situated in Kampala was the first university in the East African region to reorganize its financial system and governance starting from the 1990s, and scholars have explored what can be called its "success story" as a privately sponsored institution through "the transfer of model" from the North to the South (Darbon, 2009).
Keywords: African Research